Cellular and Molecular Targets of Waterbuck Repellent Blend Odors in Antennae of Glossina fuscipes fuscipes Newstead, 1910 - Diallo, Souleymane; Shahbaaz, Mohd; Torto, Baldwyn; Christoffels, Alan; Masiga, Daniel; Getahun, Merid N. (Frontiers in Cellular Neuroscience, 2020)
Insects that transmit many of the world’s deadliest animal diseases, for instance trypanosomosis, find their suitable hosts and avoid non-preferred hosts mostly through olfactory cues. The Waterbuck Repellent Blend (WRB) comprising geranylacetone, guaiacol, pentanoic acid and δ-octalactone derived from waterbuck skin odour is a repellent to some savanah-adapted tsetse flies and reduces trap catches of riverine species. However, the cellular and molecular mechanisms associated with detection and coding of the repellent odours remain to be elucidated. Here, we demonstrated that WRB inhibits blood feeding in both Glossina pallidipes, Austen, 1903 and Glossina fuscipes fuscipes, Newstead, 1910. Using the DREAM (Deorphanization of receptors based on expression alterations in ORs mRNA levels) technique, combined with ortholog comparison and molecular docking, we predicted the signature putative odorant receptors for the WRB in G. f. fuscipes, a non-model insect. We show that exposure of G. f. fuscipes in vivo to WRB odorant resulted in up- and down-regulation of mRNA transcript of several odorant receptors (ORs). WRB component with strong feeding inhibition altered mRNA transcript differently as compared to an attractant odour, showing these two odours of opposing valence already segregate at the cellular and molecular level. Furthermore, molecular dynamics simulations demonstrated that the predicted ligand-OR binding pockets consisted mostly of hydrophobic residues with a few hydrogen bonds but a stable interaction. Finally, our electrophysiological response shows the olfactory sensory neurons of G.f. fuscipes tuned to the tsetse repellent components in different sensitivity and selectivity.